(untitled) (Research, Society and Development, 2021)
The aim of this paper was to analyze the possibilities and limitations of vibrotactile Assistive Technology for the musical education of the deaf. We adopted the assumptions of quantitative research, through the bibliometric approach (Ângulo-Cuentas et al., 2018), as well as those of qualitative research, through the Textual Discursive Analysis (ATD) proposed by Moraes and Galiazzi (2006). The scope of the bibliometric search comprised 721 scientific articles indexed to the PubMed platform. The results showed that the scientific articles that research the intersection of music and deafness deal mainly with cochlear implants, the perception of hearing, tone and speech in human beings of both biological sexes and of varying ages, however, we noted the scarcity of research on the use of vibrotactile Assistive Technology in this area. Thus, after inserting the descriptors tactile or vibrotactile, we analyzed, through ATD, 7 articles indexed to the Pubmed platform and 5 articles indexed to the Web of Science. We conclude that, despite being incipient, the vibrotactile Assistive Technology can contribute to the musical education of the deaf.